Estimation of changes in nickel and chromium content in nickel-titanium and stainless steel orthodontic wires used during orthodontic treatment: An analytical and scanning electron microscopic study - Vandana Kararia; Pradeep Jain; Seema Chaudhary; Nitin Kararia (Wolters Kluwer Medknow Publications, 2015)
Introduction: The biocompatibility of orthodontic dental alloys has been investigated over the past 20 years, but the results have been inconclusive. The study compares standard 3 M Unitek nickel-titanium (NiTi) and stainless steel archwires with locally available JJ orthodontics wires. Scanning electron microscope (SEM) study of surface changes and complexometric titration to study compositional change was performed. Materials and Methods: Ten archwires each of group 1-3 M 0.016" NiTi, group 2-JJ 0.016" NiTi, group 3-3 M 0.019" FNx010.025" SS and group 4-JJ SS contributed a 10 mm piece of wire for analysis prior to insertion in the patient and 6 weeks post insertion. SEM images were recorded at Χ2000, Χ4000 and Χ6000 magnification. The same samples were subjected to complexiometric titration using ethylenediaminetetraacetic acid to gauge the actual change in the composition. Observations and Results: The SEM images of all the archwires showed marked changes with deep scratches and grooves and dark pitting corrosion areas post intraoral use. 3M wires showed an uniform criss-cross pattern in as received wires indicating a coating which was absent after intraoral use. There was a significant release of Nickel and Chromium from both group 3 and 4. Group 2 wires released ions significantly more than group 1 (P = 0.0). Conclusion: Extensive and stringent trials are required before certifying any product to be used in Orthodontics.